2023
DOI: 10.1371/journal.pmed.1004171
|View full text |Cite
|
Sign up to set email alerts
|

Suicidal ideation following self-reported COVID-19-like symptoms or serology-confirmed SARS-CoV-2 infection in France: A propensity score weighted analysis from a cohort study

Abstract: Background A higher risk of suicidal ideation associated with self-report of Coronavirus Disease 2019 (COVID-19)-like symptoms or COVID-19 infection has been observed in cross-sectional studies, but evidence from longitudinal studies remains limited. The aims of this study were 2-fold: (1) to explore if self-reported COVID-19-like symptoms in 2020 were associated with suicidal ideation in 2021; (2) to explore if the association also existed when using a biological marker of Severe Acute Respiratory Syndrome Co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
1
1
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 28 publications
0
2
0
Order By: Relevance
“…Regarding Toxic, according to the ALC-10 classi cation criteria, it encompasses ALCs caused by ingestion or inhalation of toxic materials (alcohol, insecticides ingestion, or adverse drug reactions), regardless of intent. It is well known that depression and suicide increased in AC [31][32][33][34][35]. Based on the authors' experience in the ER, there has been an increase in binge drinking or drug administration associated with feelings of hopelessness or suicidal intentions after the onset of COVID-19.…”
Section: Discussionmentioning
confidence: 99%
“…Regarding Toxic, according to the ALC-10 classi cation criteria, it encompasses ALCs caused by ingestion or inhalation of toxic materials (alcohol, insecticides ingestion, or adverse drug reactions), regardless of intent. It is well known that depression and suicide increased in AC [31][32][33][34][35]. Based on the authors' experience in the ER, there has been an increase in binge drinking or drug administration associated with feelings of hopelessness or suicidal intentions after the onset of COVID-19.…”
Section: Discussionmentioning
confidence: 99%
“…First, these papers demonstrate that the increases in prevalence of mental health problems expectedly were primarily concentrated in mood and anxiety conditions, but not severe mental health problems [ 8 13 ], and, some conditions even showed a decline or inconclusive findings (for example, self-harm was associated with self-reported symptoms but not serology confirmed infection in one study) [ 14 ]. Importantly, while one systematic review reported that symptoms of mood and anxiety problems increased in the first 6 months after the onset of the pandemic, the picture is less clear when participants are followed over longer periods and some changes may have been transient [ 15 17 ].…”
mentioning
confidence: 99%